Tetranychidae database for Brazil: a website for distribution and information on spider mites (Acari) - Flechtmann, Carlos H. W.; de Moraes, Regina C.b. (Zootaxa, 2018)
We present a database regarding the distribution of spider mites (Acari, Tetranychidae) in Brazil. It is available open access on the internet and hosted by the Department of Entomology and Acarology, ESALQ-USP, Piracicaba, São Paulo, Brazil, at www.lea.esalq.usp.br/tetranychidae. This database presents the first report of each species on a host plant for each State of Brazil and the corresponding reference. The home page of the site will allow searches under headings: Species, Host common name, Host species, Host Family, References and Locality.